Emergency diagnostic laparoscopy in abdominal trauma: a study of 41 patients - Marcos Félix Osorio Pagola; Julio Lasarte Ferrer; Orelvis Martínez Martínez; Libán Álvarez Cáceres; Armando Fermín Álvarez Corcuera del Pera; Denis Monzón Vega (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Background: laparoscopy is a test used in the patients with abdominal trauma with suspicion of intra-abdominal organic damage and an imminent surgical behavior. Objectives: to expose the results of the urgency laparoscopic diagnosis in the traumatic acute abdomen. Methods: an descriptive and retrospective study in patient with diagnosis of abdominal trauma to which were carried out urgency laparoscopy at the Hospital Dr. Gustavo Aldereguía Lima", from january 2001 to december 2008, when not being possible to define injury of intra-abdominal viscera performing other tests. Inclusion and exclusion criterion were applied. Results: we study 41 patients with average of 39, 2 ± 7, 7 years. Most of the studied patients were in the age range from 31 to 40 years with 21 patients (51, 2 %) the open abdominal trauma with 26 patients prevailed (63, 4 %). The masculine sex prevailed with 38 patients (92,7 %) and as much the open trauma as the closed one were more frequent in this sex with 25 patients (96,2 %) and 13 patients (86,7 %) respectively. They didn't show visceral damage during the laparoscopy 93, 3 % of the patients with closed abdominal trauma by what the surgical treatment was avoided, the same as in the patients with open abdominal trauma which had a non penetrating damage in abdominal cavity (80, 8 %). Conclusion: laparoscopic diagnosis is a useful test in patients with abdominal trauma and it avoids a considerable number of unnecessary conventional surgical treatment.